Assessing the Effects of Building Mass Configuration and Form on Solar Radiation Gain: A Hypothetical Study - Wildan Muhammad Haikal; Nedyomukti Imam Syafii (INERSIA lnformasi dan Ekspose Hasil Riset Teknik Sipil dan Arsitektur, 2026)
Urbanization has continued to grow from year to year, leading to one of its major impacts—the rising population in urban areas. This population increase is directly proportional to the growing demand for housing, which in turn drives up property prices. Therefore, government support in the form of subsidized housing for low-income communities (MBR) becomes essential. However, subsidized housing is often criticized by the public for its unsatisfactory quality. Moreover, the development of such housing is feared to exacerbate the ongoing issue of global warming, as it has the potential to increase ambient temperatures in residential areas. The objective of this study is to identify the influence of changes in building mass configuration and form on the reception of solar radiation at outdoor site surface. A quantitative research method was applied by simulating hypothetical building mass models of subsidized housing using Rhinoceros – Grasshopper – Ladybug software. The findings indicate that modifications in building mass configuration and form can reduce the amount of solar radiation received by outdoor site surface. On sites oriented west–east, the best case modification was able to reduce radiation values by up to 32.5% compared to the base case, while on sites oriented north–south, the most effective modification achieved a reduction of up to 25.3% compared to the base case.